(untitled) (Indian Journal of Animal Production and Management, 2015)
An experiment was conducted to study the influence of housing system and dietary supplementation of probiotics and enzymes on slaughter traits and meat composition in broiler rabbits. A total of 144 weaned rabbits were divided into 2 groups of 72 each and housed under conventional cage system and backyard system. The rabbits in each housing system were divided into 4 groups of 18 each and diets were supplemented with probiotics, enzymes and both. Six rabbits from each group were slaughtered at 16 weeks of age for the study. Significantly higher pre-slaughter weight, dressed weight, fore and mid cut weights and inedible offal’s were recorded by rabbits housed in cages. Among rabbits housed in cages, only weight of hind cut and length of caecum were significantly higher in rabbits fed rations supplemented with either probiotics or enzymes or both. In backyard system, pre slaughter weight, dressed weight, dressing percentage, fore cut weight, mid cut weight, head and feet weight, offal weights and length of caecum were significantly different among rabbits fed with diets supplemented with probiotics and or enzymes. Meat protein and fat percentage were significantly high in rabbits housed in cages. The protein content was significantly high in the rabbits fed rations supplemented with probiotics and both probiotics and enzymes, while the fat content was significantly high in the rabbits fed with control ration in cage reared rabbits. In backyard system, rabbits fed control ration recorded significantly lower protein and higher fat content compared to the rations supplemented with either probiotics and or enzymes..